International trends in clozapine use: a study in 17 countries. (14th May 2017) - Bachmann, C. J.; Aagaard, L.; Bernardo, M.; Brandt, L.; Cartabia, M.; Clavenna, A.; Coma Fusté, A.; Furu, K.; Garuoliené, K.; Hoffmann, F.; Hollingworth, S.; Huybrechts, K. F.; et al.
Abstract : Objective: There is some evidence that clozapine is significantly underutilised. Also, clozapine use is thought to vary by country, but so far no international study has assessed trends in clozapine prescribing. Therefore, this study aimed to assess clozapine use trends on an international scale, using standardised criteria for data analysis. Method: A repeated cross‐sectional design was applied to data extracts (2005–2014) from 17 countries worldwide. Results: In 2014, overall clozapine use prevalence was greatest in Finland (189.2/100 000 persons) and in New Zealand (116.3/100 000), and lowest in the Japanese cohort (0.6/100 000), and in the privately insured US cohort (14.0/100 000). From 2005 to 2014, clozapine use increased in almost all studied countries (relative increase: 7.8–197.2%). In most countries, clozapine use was highest in 40–59‐year‐olds (range: 0.6/100 000 (Japan) to 344.8/100 000 (Finland)). In youths (10–19 years), clozapine use was highest in Finland (24.7/100 000) and in the publicly insured US cohort (15.5/100 000). Conclusion: While clozapine use has increased in most studied countries over recent years, clozapine is still underutilised in many countries, with clozapine utilisation patterns differing significantly between countries. Future research should address the implementation of interventions designed to facilitate increased clozapine utilisation.